Analisis Gangguan Rotor Pada Motor Filter Open Circulating Cooling Water (OCCW) Di Sistem Pendingin PLTU Pangkalan Susu Unit 1 Dan 2 - Rudi Maulana; Rahmaniar (CV. Hawari, 2025)
The Open Circulating Cooling Water (OCCW) filter motor is a critical component in the power plant cooling system that functions to filter seawater before it is used to cool equipment such as the Heat Exchanger Close Circulating Cooling Water System, Hydrogen Generator Cooler, and Turbine Lubricating Oil Cooler.This study aims to analyze the rotor disturbance in the OCCW filter motor and develop solutions to improve the reliability of the cooling system.The analysis was conducted using predictive maintenance methods with vibration analysis techniques based on ISO 10816-3 standards, interviews with operators, direct observations, and operational documentation at the Pangkalan Susu Power Plant Unit 1 and 2. Vibration measurements showed abnormal values at bearing 1H (8.4 mm/s) and bearing 2H (7.5 mm/s), exceeding the ISO 10816-3 standard limit (≤7.1 mm/s) and falling into the